Individual variation in the booming calls of captive Horned Guans (Oreophasis derbianus): an endangered Neotropical mountain bird. Issue 2 (4th May 2017) - González-García, Fernando; Sosa-López, J. Roberto; Ornelas, Juan Francisco; Jordano, Pedro; Rico-Gray, Victor; Urios Moliner, Vicente
Abstract: The Horned Guan ( Oreophasis derbianus ) is a cracid restricted to cloud forests in the Sierra Madre of Chiapas in Mexico and the western-central Mountains in Guatemala. It is an endangered species and urgent conservation measures are required, such as non-invasive monitoring techniques. Here, we study individual features in the boom calls of Horned Guans. Boom calls are acoustic signals used by males during courtship and territorial displays. This call is made of seven notes, divided into two parts: an introductory section characterized by low-amplitude notes and a body section characterized by high-amplitude notes. We recorded 10 males during the breeding seasons of 2010 and 2011 in two captive populations and measured 22 acoustic variables of the calls. We used a combination of statistical analyses to test individuality in Horned Guan vocalizations. Our results showed that time-related variables – but not frequency-related traits – varied between individuals, and that individual calls showed no variation between years. Our results suggest that Horned Guan individuals can be distinguished using fine structural characteristics of their calls and that calls remain stable across years. We argue that such vocal signature could be used to track wild populations as a non-invasive technique in order to improve census data in the short and long term.